Penerapan Metode Qiroati Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Pada Kegiatan Ekstrakurikuler Di MI Nurul Ulum Sumberkatimoho Krejengan Probolinggo - Tri Wisudaningsih, Endah; Mudrikah Syarofatul Aminah, Siti (LP3M UNZAH GENGGONG, 2020)
ABSTRACT The Qur'an is the book of Allah that every believer must believe. Faith in the book of Allah is one of the three pillars of faith. Belief in the Al-Quran must be proven by studying it and teaching it to others. Allah SWT has sent down the AlQuran as the book of the last days and has become the first and foremost source of Islam. The Qur'an is the holy book of Muslims that was revealed to the Prophet Muhammad as a guide for mankind. A Muslim is required not only to be able to read the Qur'an fluently, but also to be able to understand, appreciate, and practice its contents in the behavior of everyday life. Being able to read the Al-Qur'an is an important requirement that must be mastered in studying and understanding the material of the verses of the Al-Qur'an. The qiroati method in increasing the ability to read the Koran in extracurricular activities is a method that is fundamentally oriented towards the ability to read the Koran, that learning to read the Koran is learning to listen to the recitation of the Qur'an well, learning to imitate it. , learn to recognize symbols of the written Al-Qur'an, learn to read or pronounce these symbols and learn to improve their reading according to the rules of tajwid which are applied in the framework of a process that is deliberately designed to create learning activities in individuals that are carried out outside of class hours (curriculum) to develop the potential of human resources (HR) that students have. Keywords: Qiroati Method, Ability to Read Al-Quran, Extracurricular.